PENGAWASAN KEPADA KLIEN PEMASYARAKATAN (Tantangan dan Alternatif Penyelesaian) - Yuniati Maryana Tahamata (Legal Standing : Jurnal Ilmu Hukum, 2021)
This study aims to determine the implementation of the supervision of prisoners on parole by the Community Guide. This research used descriptive qualitative method with data collection techniques in the form of observation and supported by literature studies. A prisoner undergoing parole needs to be supervised to ensure that there is no violation of the provisions of the guidance contract agreed upon by the client and the community advisor at the beginning of the mentoring period. Community Advisors as law enforcement officials are tasked with carrying out this supervision. In its implementation, there are several obstacles experienced by community counselors related to the background and competence of officers, high workloads, and coordination between community counselors and law enforcement officials. Community involvement strongly supports the successful achievement of program objectives because parole is implemented in the community. Analysis of the needs of community counselors is also needed to increase the effectiveness and professionalism of officers.